Pharmafiesta 2023 / Nur'Ainateiss Solehah Mohd Nawawi Reza, Muhammad 'Izzuddin Zamery and Dr. Gurmeet Kaur Surindar Singh - Mohd Nawawi Reza, Nur'Ainateiss Solehah; Zamery, Muhammad 'Izzuddin; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
Pharmafiesta, an annual programme organised by the Bureau of Cultural and Arts, Society of Pharmacy Students (SOPHYS), Faculty of Pharmacy, UiTM Puncak Alam, resumed in 2023 after being suspended due to online distance learning since 2021. The event took place on May 24, 2023, at DK 500, UiTM Puncak Alam. Designed not only to provide pharmacy students with a platform to showcase their skills but also to boost their self-esteem and confidence, Pharmafiesta proved to be a remarkable success.